Analisa Nilai Kalor Briket Sekam Padi Dengan Campuran Tempurung Kelapa Dan Serbuk Arang Kayu - Jatmiko Edi Siswantoa (Jurnal INOVATOR, 2018)
With the current waste of rice husk, one way to convert energy-rich agricultural waste into an easy-to-use form by combining it into briquette fuel. Briquette fuel is defined as fuel produced from organic materials. In order for the rice husk to be used to speed up the process of becoming rice husk briquettes in rice husk briquette testing, 5 (five) tests of rice husk briquettes were tested. From the results obtained by rice husk briquettes with tapioca flour adhesive has been successfully made with a mold pressure of 2 Kg / Cm2, while the briquette diameter is 100 mm with a height of 5.cm and 8. cm. The results of testing the rice husk briquette heat value obtained were 5 cm rice husk briquettes of 32,221 cal and 8 cm rice husk briquettes of 32,130 cal, briquette burning rate of 5 cm was 0.054 g / sec and for 8.cm briquettes of 0.071 g / sec, The type of Briquette 5 cm is 0.898 g / cm3 and for briquettes 8.cm is 1.052 g / cm3.